Hidrólise de Sacarose por Invertase Imobilizada em Duolite A-568 por Adsorção e Ligação Cruzada - Cabral, Bruna Vieira (2012)
In this work was studied the sucrose s hydrolysis by invertase of Saccharomyces cerevisiae immobilized by adsorption and cross-linking with glutaraldehyde, using as carrier the ion exchange resin Duolite A568. This combination of immobilization procedures has led to an increase of activity and stability of the invertase.The influence of pH on the stability of invertase with the cross-linking process was studied for the range of 3 to 7, and the biocatalyst was stable in the range of 3 to 6. The thermal stability of enzyme was studied in the range of 51 to 63ºC. The thermal deactivation model of first order described significantly the kinetics of thermal deactivation from immobilized enzyme at all temperatures studied. The activation energy of thermal deactivation process from invertase immobilized was 373.73 kJ/mol or 89.32 kcal/mol with times of half life from 8.08 hours in 51± 1ºC. The optimization of cross-linking process was studied by a Central Composite Design (CCD), where the glutaraldehyde concentration and time of cross-linking processes that maximized the enzyme activity were respectively 0.6 g/L and 6 hours. The temperature and pH of maximum activity for the immobilized enzyme were respectively 50 ± 1ºC and 4. It was studied by a Central Composite Design (CCD).The immobilized enzyme kept its activity after 60 days of storage, in acetate buffer pH 4.9 in 4 ± 2°C. The influence of sucrose concentration, residence time and temperature in the sucrose s conversion in fixed bed reactor, operating in continuous duty, with upflow was studied by a Central Composite Design (CCD). The best condition for the sucrose s conversion was: 700 g/L of sucrose concentration, 95.3 min of residence time and temperature equal to 38 ± 1ºC, reaching a conversion of 98.7%. The immobilized enzyme kept its activity during 73.58 hours by operation in fixed bed reactor, 700 g/L of sucrose concentration, 95.3 min of residence time and 38  1ºC.